Comparison of Percutaneous Kyphoplasty with or without Pedicle Screw Fixation in Osteoporotic Thoracolumbar Vertebral Fractures: A Retrospective Study - Huang, Dichao (Dis Markers, 2021)
BACKGROUND: Osteoporotic thoracolumbar compression fractures have become a great social burden due to the aging tendency of population. This study is aimed at comparing the clinical and radiological outcomes of percutaneous kyphoplasty with or without pedicle screw fixation in patients with osteoporotic thoracolumbar fractures. Hypothesis. There is a difference in clinical outcomes between percutaneous kyphoplasty with pedicle screw fixation and percutaneous kyphoplasty. METHODS: This retrospective study included 87 patients who received percutaneous kyphoplasty with or without pedicle screw fixation between October 2015 and October 2017 at Ningbo No.6 Hospital and were followed for 2 years. A total of 40 patients received percutaneous kyphoplasty with pedicle screw fixation (PKPF group), and the other 47 patients had percutaneous kyphoplasty only (PKP group). The outcomes were measured using the visual analogue scale (VAS), Oswestry Disability Index (ODI), Cobb angle (CA), and anterior vertebra height rate (AVHr), which were calculated at preoperative admission and each follow-up visit. Complications including postoperative back pain, refracture, and fixation failure were collected from medical records. RESULTS: There was no significant difference in baseline characteristics or preoperative data between the two groups (p < 0.05) but significantly better improvements in VAS, ODI, CA, and AVHr at 12- and 24-month follow-up visits in the PKPF group compared with those of the PKP group. 23 (48.9%) patients in the PKP group had complications, whereas only 5 (12.5%) patients in the PKPF group presented complications including 2 postoperative back pain and 1 fixation failure (p = 0.04). CONCLUSIONS: PKPF obtained longer correction and better improvement in VAS, ODI, and CA in patients with osteoporotic thoracolumbar vertebral fractures than PKP.